EVALUASI KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN DALAM MEWUJUDKAN KEBERHASILAN PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO TAHUN 2013 - Priyantiningtyas, Lailia (Majalah Ilmiah DIAN ILMU, 2014)
This research is going to describe and evaluate how actually work performance of the escorts of Program Keluarga Harapan is contributing to achieve successfully society empowerment programme held in Kecamatan Banyuputih Kabupaten Situbondo in 2013. Qualitative paradigm and descriptive research is used, which processing primary and secondary data. Techniques that I use to work on primary data are observation and interview, meanwhile I have documentating secondary data. From its evaluation I able to conclude that Program Keluarga Harapan held in Kecamatan Banyuputih Kabupaten Situbondo in 2013 have been contributed toward society empowerment programme.            Society empowerment concept is always upperhanded as final achievement of PKH. This means that even the programme ended people still able to recieve benefits from it. Health and education considered as the main indicator as a social modal to survive and make a betterment in the live of the society. With having strong body they able to strive and working hard, and with posessing education they have a chance to make bigger fortunes. Example of one successful PKH outcome is seen by increasing of number of working housewives as snack sellers or making a catering services. This efforts effect family economical condition, too. At last, implementation of Program Keluarga Harapan already make society to change their mindset in order to make a betterment for their lives.